Part Ι: Effects of two-stage heat treatment on densification, microstructural features and dielectric properties of CaO–MgO–SiO2 glass-ceramics with ZrO2 nucleating agents. (December 2017) - Chou, Chen Chia; Feng, Kuei Chih; Raevski, Igor P.; Chen, Haydn; Tsao, Chung-Ya; Chen, Pin-Yi; Chen, Cheng-Sao; Lu, Chun-An; Tu, Chi-Shun
Graphical abstract: Highlights: CaMgSi2 O6 glass-ceramics with ZrO2 nucleating agents using two-stage heat treatments (annealing/sintering) were investigated. Specimens annealed below critical nucleation temperature (Tcn ) and then sintered at 950 °C exhibit significant bloating phenomena. Microstructural features of CMSZ glass annealed above Tcn evidence that zirconia precipitates significantly in the CMSZ glass at the first stage of heat treatment (annealing). The second stage of heat treatment (sintering) is characterized by the rapid growth of CaMgSi2 O6 phase around the ZrO2 crystallites, indicating enhanced crystallization of nuclei due to its growth over the critical size at annealing above Tcn . Specimens annealed above Tcn and then sintered at 950 °C show high density and excellent dielectric properties. Abstract: Densification, microstructures and dielectric properties of CaO–MgO–SiO2 glass-ceramics were investigated with ZrO2 nucleating agent using two-stage heat treatment in the low temperature co-fired ceramic (LTCC) method. The amorphous cullet (abbreviated as CMSZ glass) was synthesized by mixing CaO, MgO, and SiO2 powders with ZrO2 nucleating agent, which were melted at 1500 °C before the quenching process. The results show that CMSZ glasses annealed below the critical nucleation temperature (Tcn ) and sintered at 950 °C exhibit obvious bloating phenomena. On the other hand, CMSZ glasses annealed above Tcn demonstrate that zirconia nucleation occurs at the first-stage heat treatment (annealing). The second-stage heat treatment (sintering) is characterized by the rapid crystal growth of CaMgSi2 O6 phase around the ZrO2 crystallites, indicating growth of nuclei over the critical size above Tcn . Moreover, specimens fabricated using two-stage heat treatment and annealed above Tcn exhibit appropriate microwave dielectric properties and high mechanical strength.